Primary infection by E. multilocularis induces distinct patterns of hepatic crosstalk between natural killer T and regulatory T cells in mice. (1st June 2022) - Yarahmadov, T; Wang, J; Sanchez-Taltavull, D; Brodie, T; Büchi, I; Stroka, D; Keogh, A; Alvarez, C; Beldi, G
Abstract: Objective: The larval stage of the helminthic cestode Echinococcus multilocularis can inflict tumor-like hepatic lesions that cause the parasitic disease alveolar echinococcosis (AE) in humans. Recently, opportunistic properties of the disease have been proposed based on the increased incidence in immunocompromised patients as well as on mouse models, indicating that an appropriate adaptive immune response is required for the control of the disease. However, little is known about how the local hepatic immune responses modulate the infection with E. multilocularis. Methods: In a mouse model of oral infection that mimics the normal infection route in human patients, the adaptive immune response in the liver was assessed using single cell RNA sequencing of isolated hepatic CD3+ T cells at different infection stages. Results: Single-cell RNA sequencing revealed specific temporal changes of natural killer T (NKT) cells and regulatory T (Treg) cells, indicating that these two cell types expand in the early phase and are subsequently inhibited in the late phase of infection. Receptor-ligand complex analysis via CellPhoneDB, consistently revealed high number of interactions between Tregs and NKT mainly at day 10 post infection. Relevant interactions between NKT and Treg cells at early phases include regulation of cell adhesion molecules such as integrins and selectins and TNF-dependent signalling. Immune suppressing interactions that include the checkpoint inhibitors (PD-1 and PD-L1), purinergic (ENTPD1, ADORA2A) and TGF-beta signalling are down regulated at early time points. String analysis supported these findings. Conclusion: The data indicate that early interactions between NKT and Tregs potentially promote the formation of hepatic lesions and later also contribute to immunological suppression of the resolution of parasite-induced pathology. The obtained data provide a fresh insight on the adaptive immune responses and local regulatory pathways at different infection stages of E. multilocularis in mice.